Determination of Nutrition Knowledge Levels of Teachers Working in Edirne Center - PEHLİVAN, Merve and TEVFİKOĞLU PEHLİVAN, Leyla and YALDIZ, Nihan and YEŞİLKAYA, Burcu and; M, Kıymet Pınar and; R, Kübra and; N, Ruken and IBRAIMI, Sezen (Progress in Nutrition, 2021)
Objective: This study was carried out to determine the nutritional knowledge levels of teachers working in Edirne center. Methods: A total of 389 teachers, 272 female (69.9%) and 117 male (%) volunteers. working at schools affiliated to the Republic of Turkish Ministry of National Education in Edirne Center and agreeing to participate in the study. participated in the study. The research data were collected by face-to-face interview method using a questionnaire form. The data of the research were evaluated using the SPSS 19.0 package program. Findings: The average age of teachers participating in the study is 42.67 ± 8.76 years. Teachers’ nutritional knowledge score average is 4.61 ± 1.36. There was no significant relationship between teachers’ age, gender, marital status, education, branch of study and body mass index (BMI) and their nutritional knowledge scores (p> 0.05). There is no statistically significant relationship between teachers’ access to nutritional information source, food label reading knowledge, emphasizing healthy nutrition in their lessons. and giving nutritional advice to their students (p> 0.05). Nutrition knowledge scores of teachers whose nutritional behavior affects students’ behavior were found to be significantly higher than the other group (p <0.05). Between age and nutritional knowledge score there is a significant negative relationship (r =-0.093. p = 0.067). The relationship between nutritional knowledge score and body mass index (BMI) was not found to be significant (p> 0.05). Results: In the study, the nutritional knowledge levels of teachers did not reach the expected goals for each teacher. The implementation of nutrition education programs and the frequent evaluation of the results of teachers, who shape the future and are role models for students, will lead future generations to gain healthy eating habits.